2005
DOI: 10.1128/jvi.79.16.10376-10385.2005
|View full text |Cite
|
Sign up to set email alerts
|

Early Alpha/Beta Interferon Production by Myeloid Dendritic Cells in Response to UV-Inactivated Virus Requires Viral Entry and Interferon Regulatory Factor 3 but Not MyD88

Abstract: ؊/؊ mDC cultures but was severely reduced in mDC cultures from mice lacking IFN regulatory factor 3. Our observations suggest that mDCs respond to incoming virus via a pathway that differs from the fusion-independent, MyD88-mediated endosomal pathway described for the induction of IFN-␣/␤ in pDCs. We propose that events during or downstream of viral fusion, but prior to replication, can activate IFN-␣/␤ in mDCs. Thus, mDCs may contribute to the antiviral response activated by the immune system at early time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 78 publications
(116 reference statements)
6
60
2
Order By: Relevance
“…The DREP platform differs from conventional DNA plasmids in that it encodes the alphavirus (CHIKV) replicase, which drives the production of the subgenomic RNA and thus the expression of the encoded CHIKV antigen. Moreover, DREPs also possess intrinsic adjuvant properties, since the replicase and RNA intermediates stimulate the production of type 1 interferons (IFNs) and apoptosis (32)(33)(34). Promising results have been reported for DNA replicons generated from other alphaviruses, including Semliki Forest virus (35)(36)(37), Sindbis virus (38,39), and Venezuelan equine encephalitis virus (40), when they are used for priming immunizations prior to boosting with other vaccine modalities (36).…”
Section: Hikungunya Virus (Chikv) Is An Alphavirus Of the Familymentioning
confidence: 82%
“…The DREP platform differs from conventional DNA plasmids in that it encodes the alphavirus (CHIKV) replicase, which drives the production of the subgenomic RNA and thus the expression of the encoded CHIKV antigen. Moreover, DREPs also possess intrinsic adjuvant properties, since the replicase and RNA intermediates stimulate the production of type 1 interferons (IFNs) and apoptosis (32)(33)(34). Promising results have been reported for DNA replicons generated from other alphaviruses, including Semliki Forest virus (35)(36)(37), Sindbis virus (38,39), and Venezuelan equine encephalitis virus (40), when they are used for priming immunizations prior to boosting with other vaccine modalities (36).…”
Section: Hikungunya Virus (Chikv) Is An Alphavirus Of the Familymentioning
confidence: 82%
“…Recent results from our laboratory have indeed suggested that several innate pathways are activated during SFV replication. Strong type I IFN responses are induced by SFV vectors, and they can act as adjuvant to coadministered protein on Ab production (84,85). We have also recently shown that the stimulatory effects by the SFV vectors on the innate immune system act in part through the dsRNA receptors TLR3 and Mda5 (86,87).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␣␤ bioassay was performed as described (37). IFN-␣, IFN-␤, and IL-12p40 or IL-12p70 ELISAs were performed using commercial kits distributed by PBL Laboratories and R&D Systems, respectively.…”
Section: Cytokine Titrationsmentioning
confidence: 99%